Bioequivalence and safety of a novel fentanyl transdermal matrix system compared with a transdermal reservoir system - Moore, MS, Kenneth Todd; Adams, MS, Holly D.; Natarajan, PhD, Jaya; Ariyawansa, MS, Jay; Richards, MD, Henry M. (Journal of Opioid Management, 2018)
Objectives: Fentanyl is a potent synthetic opioid used for the management of chronic pain. A newer transdermal matrix system was developed and compared with a reservoir system used in the United States. Setting: An open-label, single-center, randomized, two-period crossover study was conducted to evaluate the bioequivalence of the transdermal matrix system to the transdermal reservoir system. Seventy-four subjects completed treatment with both the reservoir system (100 μg/h) and the matrix system (100 μg/h), each applied for 72 hours. After application of the first system, subjects completed a 9-day washout and then crossed over to receive the other system for another 72 hours. Main outcome measure: Blood samples for the determination of serum fentanyl concentrations were taken in each treatment period for up to 120 hours following application. Results: The ratios of geometric means for maximum fentanyl concentration (Cmax) and area under the concentration-time curve (AUClast and AUC∞ ) were 106 percent, 110 percent, and 110 percent, respectively. The 90% confidence intervals for the ratios of the geometric means were contained within the bioequivalence criteria of 80-125 percent. The matrix system adhered well to skin. Systemic and topical safety profiles were comparable between treatments. Conclusions: The transdermal fentanyl matrix system adhered well, was well tolerated, and produced systemic exposures of fentanyl that were bioequivalent to the reservoir system.